Infiltrative Lipomatosis in the Neck and Colon of a Spanish Pure Breed Horse - Briceño, A. Morales; Sanchez, A. Méndez; Arevalo, J. Perez (Brazilian Journal of Veterinary Pathology, 2015)
The aim of this study was to report a case of infiltrative lipomatosis in the neck and colon in a horse. A 12-year-old male Spanish Pure Breed Horse with deformation of dorsal neck, weighing 650 kg, with a history of acute colic for approximately 24 hours. Euthanasia was undertaken. A necropsy revealed general excessive lipid accumulation in subcutaneous tissue in the dorsal neck. The pelvic flexure of the large colon was found to be displaced into the right cranial abdomen. A large multinodular and multifocal infiltrative fatty mass coalescing was present in a 1.5 m segment of colon with severed lipomatosis; the small intestine proximal to this lesion was moderately distended with fluid. Lipomatosis in the dorsal neck was observed, characterized by diffuse thickening of the subcutis by mature adipose tissue. In conclusion we report a case of severed infiltrative lipomatosis intestinal in large colon and neck.